Otimização simultânea da reconfiguração e da alocação de bancos de capacitores em sistema de distribuição radiais utilizando uma estratégia multipartida - Montsutsumi, Márcio Masatoshi [UNESP] (2017)
The purpose of this research is to develop a tool for optimization in power system distribution that uses meta-heuristic based on a multi-start methodology to reconfigure and allocate fixed and switched capacitor banks to obtain the radial topology that presents the lowest operating cost. To find initial radial topologies for system reconfiguration, the Prim algorithm was applied and to the current solution an improvement process called “neighborhood search” was performed. The improved system is subjected to a capacitor allocation algorithm showing that it is possible to get a radial topology that presents more economic cost of operation. As a proposal of the multi-start methodology, the procedure is repeated until a desired stop criterion, then several solutions are generated and the best one can be the solution of the problem. All programs were written in C ++ and applied to systems of 69 nodes, 84 nodes and 135 nodes.